Multi-source remote sensing workflow (PlanetScope and Sentinel-1/2) applied to LULCC analysis (2016–2024) in the SDERM-CGSM Ramsar Site, Colombia - Cristian C. Montes-Chaura; Lina Latorre-Conde; Dayron Quintero-Rodriguez; Brayan Estupiñan-Angarita; José Rodriguez-Bolaños; Jesús Emilio Pinto-Lopera (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Superovulation with eCG alone or combined with the GnRH analogue buserelin improves transferable embryo production in weaned sows without affecting Day 6 embryo morphological, cellular, and transcriptomic parameters - Adelina Lopez-Jara; Manuela Garcia-Canovas; Henar Gonzalez-Ramiro; Carolina G. Cabrera-Gomez; David Gascon-Collado; Paula Blanco-Cueto; Maria A. Gil; Cristina Cuello; Inmaculada Parrilla; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano (Animal Reproduction Science, 2026)

Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Windstorms increase benthic-pelagic coupling and nutrient outwelling from shallow coastal wetlands - Alfonso Corzo; Valle Perez-Rodriguez; Sara Haro; Sokratis Papaspyrou; Sandra Rizzo-Calderón; Ma Dolores Jimenez-Lopez; Emilio Garcia-Robledo (Frontiers in Marine Science, 2026)
Expected higher intensity and frequency of extreme climatic events is likely to affect considerably coastal shallow areas. We studied the impact of a windstorm event (WSE) on relevant biogeochemical characteristics in the water column and intertidal sediments of the inner Cadiz Bay (Spain), as a model for shallow coastal environments. Samples were collected before, during and after a WSE in two sites with different sediment characteristics, sandy and muddy, located in opposed sides of the inner bay to cover maximum variability. Total suspended solids (TSS), chlorophyll a (Chla) and most dissolved inorganic nutrients increased transiently in the water column during WSE, showing an evident transfer of matter from the sediment. TSS and Chla in water column were linearly related among them and with wind speed, while concentration of inorganic nutrients was not. This difference suggests that the concentrations of inorganic nutrients in the water column were not the direct result of the release during resuspension, but that further biogeochemical processing occurs in the water column. TSS and Chla estimated by Sentinel-2 imagery confirmed the impact on the water column, but also a considerable degree of spatial heterogeneity. WSE affected sediment O 2 vertical distribution, net metabolism, Chla, organic carbon, total nitrogen and pore water NH 4 + and PO 4 3- in different degree depending on sediment characteristics and hydrodynamics conditions. Overall, these changes were transitory, returning the system very soon to pre-WSE conditions. Clearly WSE increased benthic-pelagic coupling in shallow coastal areas, increasing resuspension and exchange of nutrients between the sediment and the water column. During WSE, the outwelling from these shallow environments can increase considerably, likely affecting coastal productivity.

Developing a novel topographic-based precision restoration framework for Drylands Ecosystems - Janira Fernandez-Galera; Yolanda Canton; Mariano Moreno-de-las-Heras; Juan Martínez-Sánchez; Sonia Chamizo; Emilio Rodriguez-Caballero (Ecological Engineering, 2026)

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

Changes in gut microbiota signatures associated with the epidemiological dynamics of wild European rabbits facing haemorrhagic disease outbreaks - Carlos Rouco; Xavier Triadó-Margarit; Joana Abrantes; Ana M. Lopes; Tereza Almeida; Julio Isla; Gabriela de la Fuente; Oscar Rodriguez; Emilio O. Casamayor (Veterinary Microbiology, 2025)

Gene dysregulation impairs placental angiogenesis in allogeneic pig pregnancies - Cristina A. Martinez-Serrano; Josep M. Cambra; Manuel Alvarez-Rodriguez; Inmaculada Parrilla; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez (Animal Reproduction Science, 2025)

Interleukin-6 supplementation during in vitro maturation improves developmental competence of in vitro fertilized porcine oocytes - Manuela Garcia-Canovas; Adelina Lopez-Jara; Alejandro Gonzalez-Plaza; Inmaculada Parrilla; Heriberto Rodriguez-Martinez; Cristina Cuello; Emilio A. Martinez; Maria A. Gil (Theriogenology, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Ecohydrological processes can predict biocrust cover at regional scale but not global scale - Ning Chen; Siqing Wang; Liping Yang; Defei Liang; Zhengwei Ren; Xudong Liu; Longwei Dong; Jingyao Sun; Emilio Rodriguez-Caballero; Bettina Weber; Caroline A. Havrilla; Emilio Guirado; et al. (Plant and Soil, 2025)

Deciphering immune tolerance in allogeneic pig pregnancy - Josep M. Cambra; Cristina A. Martinez-Serrano; Heriberto Rodriguez-Martinez; Juan M. Vazquez; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Inmaculada Parrilla (Theriogenology, 2025)

An automatic procedure for mapping burned areas globally using Sentinel-2 and VIIRS/MODIS active fires in Google Earth Engine - Aitor Bastarrika; Armando Rodriguez-Montellano; Ekhi Roteta; Stijn Hantson; Magí Franquesa; Leyre Torre; Jon Gonzalez-Ibarzabal; Karmele Artano; Pilar Martinez-Blanco; Amaia Mesanza; Jesús A. Anaya; Emilio Chuvieco (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Challenges and Security Risks in the Red Sea: Impact of Houthi Attacks on Maritime Traffic - Emilio Rodriguez-Diaz; J. I. Alcaide; R. Garcia-Llave (Journal of Marine Science and Engineering, 2024)
This study examines the significant impact of Houthi insurgent activities on maritime traffic within the strategic Red Sea and Suez Canal routes, essential conduits for global trade. It explores the correlation between regional instability, exemplified by Houthi actions from 19 November 2023 to 5 February 2024, and changes in maritime traffic patterns and operational efficiency. This study seeks to answer a critical question in transport geography: how does regional instability, exemplified by Houthi insurgent activities, affect the maritime traffic patterns and operational efficiency of the Red Sea and Suez Canal? Using descriptive statistics, qualitative analysis, and geospatial methods, this research highlights recent trends in maritime traffic and incidents, revealing spatial and geopolitical challenges in this crucial trade route. The findings indicate a notable decline in maritime activity in the Gulf of Aden and Suez Canal due to security concerns from Houthi attacks, prompting a significant shift to alternative routes, particularly around the Cape of Good Hope. This shift underscores the broader implications of regional instability on global trade and the importance of maintaining an uninterrupted maritime flow. This study also emphasizes the economic ramifications, such as increased operational costs and freight rates due to longer transit times and enhanced security measures. This research concludes with a call for improved maritime security protocols and international cooperation to protect these strategic maritime pathways. It contributes to the discourse on transport geography by quantifying the direct impacts of regional conflicts on maritime logistics and proposing strategies for future resilience, highlighting the interconnected nature of global trade and security and the need for collective action against evolving geopolitical challenges.

Phenolic profile, cheminformatics, and antiplatelet aggregation activity of orange and purple sweet potato (Ipomoea batatas L.) storage roots - Lyanne Rodriguez; Óscar Adrian Muñoz-Bernal; Eduardo Fuentes; Emilio Alvarez-Parrilla; Iván Palomo; Abraham Wall-Medrano (Food Chemistry, 2024)

Reproductive physiology of the boar: What defines the potential fertility of an ejaculate? - Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano; Manuel Alvarez-Rodriguez; Emilio A. Martinez; Jordi Roca (Animal Reproduction Science, 2024)

Vitrification of pig embryos dysregulates the microRNA transcriptome profile - Cristina Cuello; Alejandro González-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Heriberto Rodriguez-Martinez; Maria A. Gil; Emilio A. Martinez (Theriogenology, 2024)

Benthic metabolism and nutrient dynamics of a hyperturbid and hypernutrified estuary - Valle Perez-Rodriguez; Alfonso Corzo; Sokratis Papaspyrou; Stefanie Anne van Bergeijk; Cesar Vilas; José Pedro Cañavate; Emilio Garcia-Robledo (Frontiers in Marine Science, 2024)
The biogeochemical role of the sediments in the Guadalquivir River estuary, a vital region in the SW Iberian Peninsula, has been considerably neglected. The benthic microalgae (microphytobenthos, MPB) inhabiting the sediment surface could contribute to the autochthonous primary production and influence nutrient recycling in this hyper-turbid and hypernutrified estuary. Sediment–water column fluxes of O 2 and dissolved inorganic nitrogen species (DIN = NH 4 + + NO 3 − + NO 2 − ) were assessed in laboratory incubations of sediment cores from Bonanza (mouth) and Lebrija (middle) during a 1-year study. Vertical profiles down to the 10-cm depth of photosynthetic pigments, organic C, total nitrogen, DIN, Fe 2+ , SO 4 2− , and dissolved inorganic carbon (DIC) were also measured. Chlorophyll a in the sediment surface was higher at the estuarine mouth, exhibiting a seasonal pattern at both sites with highest values in winter and lowest in summer. Net community production (NCP) was higher in Bonanza compared with Lebrija and showed positive values most of the year, indicating that MPB contributed to the overall autochthonous primary production of the estuary. Seasonal changes in chlorophyll a and NCP were not parallel, suggesting different ecological controls. The sediment was generally a net sink of NO 3 − and NH 4 + in both sites, with several fold higher rates for NO 3 − uptake. MPB N demand could account for the entire sediment DIN uptake in Bonanza and 21% in Lebrija. The remaining high NO 3 − uptake rates indicate that they sustain elevated sediment denitrification rates. In contrast, rates of anaerobic oxidation of organic matter by Fe reduction and SO 4 2− reduction, estimated from Fe 2+ and SO 4 2− vertical concentration profiles, were several orders of magnitude lower than the estimated water column-dependent denitrification rates. Overall, this study shows the importance of MPB in the Guadalquivir Estuary and the potential dominant role of denitrification in the anaerobic mineralization of organic matter.

Long-range transport and microscopy analysis of Sangay volcanic ashes in Ecuador - Daniel Moran-Zuloaga; Wilson Merchan-Merchan; Emilio Rodriguez-Caballero; Maurizio Mulas; Philip Hernick (Air Quality, Atmosphere & Health, 2024)
This study aims to conduct a spatiotemporal analysis of the long-range transportation of volcanic ashes that originates from the eruption of the Sangay volcano and reached Guayaquil during the months of June 2020; September 2020; and April 2021. The particulate matter data (PM 2.5 ) was obtained using a low-cost air quality sensor. During the wet season of 2020 (Jan–May), PM 2.5 average concentrations were 6 ± 2 μg m −3 while during the dry season of 2020 (July–Nov), PM 2.5 average concentrations were 16 ± 3 μg m −3 in Guayaquil. The most prominent plumes occurred on September 20th of 2020, a month with no rain but high wind speeds created by the Andes Mountain topography to the coast. During this event, PM 2.5 concentrations started at 12:00 UTC-5 in a volcanic plume event that lasted 4 h with a maximum peak of 133 + 40 μg m −3 . Electron microscopy of selected samples showed that the ashes of the three eruptions may differ in size and morphology. EDX analysis reveals that the ash contains certain elements—C, Si, Na, Mg, Al, Ca, S, and Fe—in similar proportions. In summary, this study remarks on the meteorological role and the long-range transport of Sangay volcanic ashes.

Ambient temperature modulates body weight changes in patients with advanced oncological diseases and anorexia cachexia syndrome - Paloma Encinas; Jose Luis Rodriguez-Arias; Luis Miguel Luengo Pérez; Daniel Cortizo; Emilio Gutierrez (International Journal of Biometeorology, 2023)
Objective To assess the impact of ambient temperature (AT) on the evolution of bodyweight in patients with heterogeneous types of cancer in advanced stages of the disease (stages III and IV) and anorexia- cachexia syndrome (ACS). Methods A prospective naturalistic multicenter study of patients undergoing oncological treatment at four hospitals during a three-year period (2017–2020) in the Autonomous Community of Extremadura in southwestern Spain with a continentalized Mediterranean climate of mild and relatively rainy winters, and particularly hot and sunny summers. Bodyweight changes were obtained from the medical records of 84 oncological patients (59 men and 25 women, age range 37–91 yrs). Mean monthly AT was used to examine the association of weight changes across cold and warm bimesters -BIMs (December and January, vs. July and August), Trimesters -TRIMs (July to September vs. December to February), and Semesters -SEMs (May to October vs. November to April). Weight changes between two consecutive weight measures were categorized as weight gain, weight loss, or no weight change. Differences across cold and warm seasons were analysed using parametric (ANOVA), and nonparametric statistics (Chi-square and binomial z tests). An alpha-rate of 0.05 was used for all analyses. Results A weight loss trend was observed during BIMs cold periods in comparison to warm ones ( p 0.04). However, differences in average bodyweight were not significant. The negative impact of cold periods was more marked in men than in women, ( p = 0.05; p = 0.03, for cold vs. warm BIMs and TRIMs, respectively). In contrast, significantly higher weight gain percentages were found in women during warm TRIMs and SEMs ( p = 0.03, and p = 0.01, respectively). As for the number of patients dying during the study ( N = 56; 39 men, 17 women), there were a significant interaction between temperature (cold/warm), and mean weight F ( 1, 499) = 6.06, p = 0.01, which revealed a pattern of weight loss in the cold semester as opposed to weight gain during the warm SEM months. Conclusions AT temperature modulated body weight changes in patients with advanced oncological disease and ACS. Two main limitations of the study were the absence of information on diets as a moderating factor of weight loss/gain, and the lack of the patients’ weight measurements closest to the date of diagnosis prior to admittance to the study. As for the practical implications, it remains to be seen whether an adjunctive heat supply will serve a buffering effect on weight loss during colder seasons for patients with advanced cancer and ACS.

Cryotop vitrification of large batches of pig embryos simultaneously provides excellent postwarming survival rates and minimal interference with gene expression - Alejandro Gonzalez-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez; Cristina Cuello (Theriogenology, 2023)

Behind the Scenes for the Designation of the Corales de Profundidad National Natural Park of Colombia - David Alonso; Martha Vides-Casado; Francisco Arias-Isaza; Hernando Zambrano; Emilio Rodriguez; Venus Rocha-Gutierrez; Pilar Herron; Anny Castillo (Frontiers in Marine Science, 2021)
Deep-water environments make up 64% of the world’s oceans (nearly 202 million km 2 ). In the past, the belief that this environment represented one of the most stable and unproductive ecosystems on the planet has been refuted by scientific research and the interest of potential productive sectors evaluating seabed resources. Human activities that threaten the health of deep-sea threats are uncontrolled and unregulated fishing, deep-sea mining, oil spills, marine litter, and climate change. With recent advances in technology, the study of deep-sea coral communities is a growing subject. The deep-sea corals are long-lived, slow-growing, and fragile systems, making them especially vulnerable to physical damage. In the last 40 years, Colombia has discovered these communities’ existence scarcely distributed in its territorial waters. A representative and irreplaceable sample of deep-sea coral formations triggered in 2013 the establishment of the Corales de Profundidad National Natural Park, a Marine Protected Area (MPA), which holds 40% of the marine biodiversity known in the Colombian Caribbean continental shelf-slope break. The MPA’s essential ecological value is the Madracis myriaster species’ presence as a primary habitat-forming organism, a unique habitat for the Caribbean and the world. Here we describe the MPA creation process in three phases. Firstly, in the provisioning phase, three main threats from human activities are identified. Secondly, in the preparation phase, the area’s conservation objectives and management category are defined, and the negotiation process with the fishing, communications, and oil and gas economic sectors is described. Lastly, in the designation phase, three MPA scenario proposals were evaluated, assessing the minimum distance, the possible effects of activities in the area as the main criteria for the buffer zone and the management of possible future impacts. As a result, the most extended boundary was adopted, guaranteeing these communities’ conservation despite the limited information to carry out a complete planning process. The MPA designation is considered the first experience of deep communities in the Southern Caribbean and an example that it is possible to have effective conservation agreements with economic sectors.

Umbilical cord: an allogenic tissue for potential treatment of COVID-19 - Hugo C. Rodriguez; Manu Gupta; Emilio Cavazos-Escobar; Saadiq F. El-Amin; Ashim Gupta (Human Cell, 2021)

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

CA19-9 capability as predictor of pancreatic cancer resectability in a Spanish cohort - Marta Herreros-Villanueva; Lourdes Ruiz-Rebollo; Mario Montes; Mario Rodriguez-Lopez; María Francisco; Joaquín Cubiella; Eduardo Iyo; Emilio Garabitos; Emma Martínez Moneo; Maider Martos; Enrique de Madaria; Ibon Martínez-Arránz; et al. (Molecular Biology Reports, 2020)

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz - José L. Rueda; Emilio González-García; Cinja Krutzky; Francisco J. López-Rodriguez; Gerardo Bruque; Nieves López-González; Desiree Palomino; Ricardo F. Sánchez; Juan Tomás Vázquez; Luis M. Fernández-Salas; Victor Díaz-del-Río (Marine Biodiversity, 2016)

Effects of acute and repeated cocaine on markers for neural plasticity within the mesolimbic system in rats - Nieves Rodriguez-Espinosa; Emilio Fernandez-Espejo (Psychopharmacology, 2015)

Changes in the peripheral blood and bone marrow from untreated advanced breast cancer patients that are associated with the establishment of bone metastases - Leandro Marcelo Martinez; Valeria Beatriz Fernández Vallone; Vivian Labovsky; Hosoon Choi; Erica Leonor Hofer; Leonardo Feldman; Raúl Horacio Bordenave; Emilio Batagelj; Federico Dimase; Ana Rodriguez Villafañe; Norma Alejandra Chasseing (Clinical & Experimental Metastasis, 2014)

Effect of salinity on egg hatching, yolk sac absorption and larval rearing of Senegalese sole ( Solea senegalensis Kaup 1858) - Emilio A. Salas Leitón; Ana Rodriguez‐Rúa; Esther Asensio; Carlos Infante; Manuel Manchado; Catalina Fernández‐Díaz; José P. Cañavate (Reviews in Aquaculture, 2012)
Assays carried out under laboratory‐controlled conditions revealed that eggs of Senegalese sole, Solea senegalensis Kaup 1858, incubated at 10, 18, 27 and 33 grams per litre (g L −1 ) reached their maximum hatching rates (above 80%) 48 h after incubation. In contrast, hatching was significantly delayed (24 h) and completely failed when the salinity was set at 5 and 0 g L −1 , respectively. Newly hatched and early‐developing yolk sac larvae presented similar survival rates 3 days after hatching (DAH) when exposed to salinities of 10, 18, 27 and 33 g L −1 . Larvae incubated at 5 g L −1 salinity died a few hours after hatching once they were released from their respective chorions. The notochord length was unmodified by salinity 5 DAH. Nevertheless, an overall lower myotomal height and a putative delay in the depletion of yolk sac were found in larvae reared at 10 g L −1 . This anomaly in overall larval development became more pronounced with the occurrence (100% of analysed larvae) of mouth deformities and a lack of functionality under 10 g L −1 salinity. Transferring 2 DAH larvae from 33 g L −1 (exhibiting normal mouth development) to a medium with a salinity of 10 g L −1 had no effect on first feeding, weight and metamorphic index. Overall our results indicate the existence of a key time window (0–2 DAH) in which a salinity value higher than 10 g L −1 is required to achieve adequate mouth development and further functionality of larvae. The present work represents a valuable contribution to the sole industry, opening new possibilities in hatchery management practices.

Role of cannabis and endocannabinoids in the genesis of schizophrenia - Emilio Fernandez-Espejo; Maria-Paz Viveros; Luis Núñez; Bart A. Ellenbroek; Fernando Rodriguez de Fonseca (Psychopharmacology, 2009)

Sensorimotor gating in mice is disrupted after AM404, an anandamide reuptake and degradation inhibitor - Emilio Fernandez-Espejo; Beatriz Galan-Rodriguez (Psychopharmacology, 2004)

Response of Parasitoids Dendrosoter protuberans and Cheiropachus quadrum to Attractants of Phloeotribus scarabaeoides in an Olfactometer - Carlos Lozano; Emilio Gonzalez; Aranzazu Peña; Mercedes Campos; M. Teresa Plaza; Miguel Rodriguez; Isidoro Izquierdo; Juan Tamayo (Journal of Chemical Ecology, 2000)

Effect of zinc on aminopeptidase N activity and L-threonine transport in rabbit jejunum - María-Carmen Rodriguez Yoldi; José-Emilio Mesonero; María-Jesús Rodriguez Yoldi (Biological Trace Element Research, 1996)

Inhibition of L-threonine intestinal absorption in rabbits by cadmium - José Emilio Mesonero; María-Carmen Rodriguez Yoldi; María-Jesús Rodriguez Yoldi (Biological Trace Element Research, 1996)

Effect of zinc on L-threonine transport across the jejunum of rabbit - María-Carmen Rodriguez Yoldi; José-Emilio Mesonero; María-Jesús Rodriguez Yoldi (Biological Trace Element Research, 1993)